Analisis Manajemen Resiko Terhadap Keselamatan Kerja Karyawan Di PTPN IV Regional I Kebun Ambalutu - Nugraha, Hasybi Abdillah; Aslami, Nuri (Journal of Innovation in Management, Accounting and Business, 2024)
Occupational safety is one of the important aspects in the industrial world, especially in companies that have a high potential risk of work accidents. In Indonesia, plantation companies such as PTPN IV Regional I Kebun Ambalutu, which is engaged in the oil palm plantation sector, face major challenges in maintaining employee safety. This study aims to analyze risk management concerning employee safety at PTPN IV Regional I Kebun Ambalutu. Using observational methods during an internship program, the author participated in various activities, including preparing documents for external audits, conducting safety awareness campaigns for the local community, and contributing to tasks in the Certification System Department (DSS). The analysis reveals that the company has effectively implemented risk management practices for employee safety through measures such as workplace accident investigations, employee training and safety education, and the provision of personal protective equipment (PPE). In addition, although safety training has been conducted, some employees feel less prepared to deal with more complex emergency situations. This commitment not only enhances employee well-being but also contributes to improved productivity and operational sustainability.